Objectively measured adherence to physical activity among patients with coronary artery disease: Comparison of the 2010 and 2020 World Health Organization guidelines and daily steps - Eser, Prisca; Gonzalez-Jaramillo, Nathalia; Weber, Selina; Fritsche, Jan; Femiano, Riccardo; Werner, Charlotte; Casanova, Flurina; Bano, Arjola; Franco, Oscar H.; Wilhelm, Matthias (Frontiers in Cardiovascular Medicine, 2022)
Background Tailored recommendations for patients after percutaneous coronary interventions (PCI) need physical activity (PA) to be objectively measured and assessed for adherence to guidelines. The recent WHO guidelines removed the daily recommended bout duration, while the potential impact of this change on patients after PCI remains unclear. Aim We evaluated prevalence estimates of adherence to PA recommendations among patients after PCI across the 2010 [≥30 min moderate- to vigorous-intensity PA (MVPA) at ≥ 10-min bout duration] and 2020 WHO guidelines (≥30 min of MVPA of any bout duration), as well as 7,500 and 10,000 steps. Methods We conducted an observational longitudinal single-center study with patients after PCI for chronic or acute coronary syndrome (ACS); maximal age 80 years. Wrist-worn accelerometers recorded participants’ PA data from the evening of hospital discharge over the next 18 days. Results We analyzed data from 282 participants with sufficient minimum wear time (7 days of ≥12 h), including 45 (16%) women; and 249 (88%) with ACS. Median wear time was 18 (17, 18) days. Median participant age was 62 (55, 69) years. Fifty-two participants (18.4%) fulfilled 2010 WHO guidelines and 226 (80.1%) fulfilled the 2020 WHO guidelines. Further, 209 (74.1%) participants achieved ≥7,500 steps/day and 155 (55.0%) performed ≥10,000 steps/day. Conclusion Among participants after PCI, most MVPA was accumulated in bouts <10 min, leading to a fourfold discrepancy between participants fulfilling the 2010 and 2020 WHO PA recommendations. The number of steps/day may be a valid proxy to recent WHO PA recommendations as it is not dependent on the bout-length definition. Clinical trial registration [ClinicalTrials.gov], identifier [NCT04663373].